PENGARUH METODE RESITASI (PENUGASAN) TERHADAP HASIL BELAJAR IPA SISWA KELAS V SDN 2 KEKERI TAHUN AJARAN 2021/2022 - Silvia Ika Januarti; Muhammad Liwa Ilhamdi; Husniati Husniati (Program Studi PGSD, FKIP, Universitas Mataram, 2021)
This study aims to determine the effect of the recitation (assignment) method on science learning outcomes for V grade students in the 2021/2022 academic year. This research is a Quasi-Experimental type of research with the Nonequivalent Control Group Design type. The population in this study were all V grade students at SDN 2 Kekeri totaling 36 students and the technique used in sampling was saturated sampling technique where class VA was the control class and class VB was the experimental class. The data collection technique in this study was a test of students' cognitive learning outcomes in science. Data on students' cognitive science learning outcomes were analyzed using the t-test (t-test) Separated Variance with a significant level of 5%. Based on the results of the statistical analysis of the t-test, the results of tcount > ttable are 4,680 > 2,034, which means that there is an influence of the recitation method (assignment) on the science learning outcomes of V grade students of SDN 2 Kekeri Academic Year 2021/2022. The difference is 15.74 (78.29-62.55). Based on the calculation of the gain test on students' science learning outcomes, which is indicated by an average <g> of the experimental class of 0.562 in the medium category, higher than the control class average, which is 0.288 in the low category. Thus, it strengthens the conclusion that there is an effect of using the recitation method (assignment) on the science learning outcomes of fifth grade students of SDN 2 Kekeri Academic Year 2021/2022.